Roasted coffee bean production a plant design - Jovellana, John Andrew Kane P.; De Guzman, Charlene A.; Trivino, Monica Louise T. (College of Engineering, University of the Philippines Diliman, 2016)
To address the issue of growing fuel demand in the Philippines and the mandatory blending of ethanol to gasoline up to 20% by the year 2020, a bioethanol production plant was designed to process 5901 kg/h of crude glycerol (basis of 85% purity) into 2216 kg/h of 99.5% by weight anhydrous ethanol using batch fermentation by Escherichia coli SS1 as the bioconversion route. The objective is to conduct a technical and economic feasibility study of establishing the said facility in the Philippines.Analysis of the local and global markets for crude glycerol and bioethanol indicate that there is growing demand for bioethanol and excess supply of crude glycerol. A preliminary economic analysis of raw material and product prices showed that the plant will gain a positive economic potential. The plant is to be situated in Brgy. Sta. Rita, Batangas City, a bustling industrial zone accessible to glycerol suppliers and bioethanol clients in the region. The synthesis of the process flowsheet included considerations of the mode of operation, input-output structure, recycle structure, separation system, and heat exchange network.Process flowsheets of major equipment (PFD) were developed for the feed preparation, fermentation, and product recovery section using SuperPro Designer, ChemSep, and CHEMCAD simulation software. The plant consist of three sections: Feed Preparation, Fermentation, and Product Purification sections, with the fermentation section in batch mode and the other two section is continuous operation. It is designed to operate at full capacity for 330 days and 288 batches per year.Major equipment in the process flowsheets include static equipment such as storage and holding tanks, fermenters, heat exchangers, vessels, centrifuge, fire heater, and distillation column, and rotating equipment such as pumps and blowers for handling liquids and gases respectively. Packaged equipment include the EET glycerol purification system and molecular sieve adsorption for ethanol dehydration. The detailed design of 41 major static and rotating equipment in the three section of the plant was conducted to obtain estimates of purchase costs.The utilities required by the process include 10,400 kg/h low-pressure steam for heating, 771,778 kg/h cooling water for cooling, 28,583 kg/h demineralized water, 640 kWh/h electricity, and 3,761 kg/h air for combustion. Chemicals used in the fermentation section include corn steep liquor as the minimal media, E. coli inoculum, sulfuric acid and caustic for pH adjustments, anti-foaming agent, water for cleaning and nitrogen gas for purging and inerting.Basic equipment and piping layout and line sizing calculations for all process streams in the flowsheet were used in the detailed design of pumps and blowers. Line sizes and instrumentation are also incorporated in the piping and instrumentation (P&ID) diagrams. Safety considerations in the process include basic process controls, alarms and interlocks or safety instrumented systems (SIS), pressure relief systems, and hazard and operability (HAZOP) study. Adjustments in the controls and instrumentation were added to the P&IDs accordingly. The presence of hydrogen gas in the fermenters poses the great fire and explosion risk and was addressed in the HAZOP study.The total capital investment required was calculated from the equipment purchase costs, while the total product cost was derived from raw material and product prices, utility consumption, and labor and maintenance costs. Fro the economic analysis, it is assumed that the plant is to be constructed in 2018, with 2 years of construction and 15 years of operation. The plant required a total capital investment of US dollar 11.11 million. The fermenters accounted for 83% of the purchase cost of equipment. The total revenue from sales is US dollar 39.22 million, assuming full capacity, while the total raw materials, labor, and utility costs are US dollar 12.85 million, US dollar 0.54 million, and US dollar 4.71 million, respectively. Steam cost accounted for 73% of the utility costs. The annual total product cost is US dollar 23.62 million, leaving a net annual profit of US dollar 15.60 million. Results of the profitability analysis showed an internal rate of return of 7.80% and a net present value of US dollar -1.60 million with no payback period. Hence, the project is not economically feasible under the assumed market conditions and design basis. A scenario analysis on extending the initial glycerol titer to higher than 47 g/L, and will reach the minimum acceptable internal of return of 15% at concentrations higher than 90 g/L, a target for research and development in making the large-scale process a feasible investment.